Upaya Meningkatkan Keaktifan dan Keterampilan Menulis Recount Text melalui Strategi Discovery Learning dengan Teknik BIN KPK - Ni'matulloh, Ni'matulloh (Universitas Muhammadiyah Magelang, 2020)
The purpose of this Classroom Action Research is to improve the activeness and the writing skills of recount text in the class VIII B students of SMP Negeri 1 Banjarnegara through the Discovery Learning strategy with the BIN KPK technique. The research method used was Classrooom Action Research. The subject of this study used 32 students of class VIII B SMP Negeri 1 Banjarnegara in the even semester of the 2019/2020 academic year, consisting of 12 male students and 20 female students. The results show that through the use of the Discovery Learning strategy with the BIN KPK technique, the activeness of students in the learning process has increased significantly when compared to the results of observations in pre-cycle, cycle I and cycle II, namely 14, 25, 30. or 43.75%, 78.13%, 93.75%, and learning outcomes (writing recount text skills) of students experienced an increase in each cycle. The initial completeness according to the indicators of the pre-cycle 13 students or 40.63%, in the first cycle the completeness according to the indicators of students became 26 students or 81.25%, while in the second cycle the completeness of students became 31 students or 96.87%. This method becomes reference for other teachers in teaching genres.